“Rerajahan Kawisesan” dalam Teks “Ajiblêgodawa”: Sebuah Kajian Etnosemiotika - I Wayan Rasna (Jurnal Kajian Bali (Journal of Bali Studies), 2015)
This study aims to analyze the form, function, and meaning rerajahan kawisesanin the Text of AjiBlêgodawa. This research was carried outby using ethno-semiotic approach, the method of text analysis linking text reading, in the form of images (rerajahan) to explore the meaning of the community readers. Data were collected through library research, observation, interviews, and documentation. Data were analyzed by means of: 1) identification rerajahan as nonverbal text, 2) ethno-semiotic analysis, phase I (denotative) and phase II (connotative). The results showed that: 1) the form of rerajahan kawisesanin AjiBlêgodawa Text consist of: a) Kaputusan Aji Kundalini, b) Kanda Pat, c) Surya Ireng, and d) Windu Ngadeg; 2) rerajahan kawisesan function is body and soul protector in order to avoid magical distress; 3) the meaning of kawisesan image is to keep the peace.